2013
DOI: 10.1002/app.39691
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and adsorption properties of diethylenetriamine‐modified chitosan beads for acid dyes

Abstract: This work has demonstrated that the novel chitosan derivative, synthesized by phase transition and grafting diethylenetriamine, has a great potential for the adsorption of acid dyes from aqueous solutions. Four acid dyes with different molecular sizes and structures were used to investigate the adsorption performance of diethylenetriamine-modified chitosan beads (CTSN-beads). Results indicated that the adsorption of dyes on CTSN-beads was largely dependent on the pH value and controlled by the electrostatic at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Yan et al . studied a more complex adsorption phenomenon, in which two model dyes (AO7 and AG25) were competitively adsorbed onto beads of chitosan grafted with diethylenetriamine . The Langmuir and Freundlich equations were run for fitting.…”
Section: Discussionmentioning
confidence: 99%
“…Yan et al . studied a more complex adsorption phenomenon, in which two model dyes (AO7 and AG25) were competitively adsorbed onto beads of chitosan grafted with diethylenetriamine . The Langmuir and Freundlich equations were run for fitting.…”
Section: Discussionmentioning
confidence: 99%
“…Yan et al studied a more complex adsorption phenomenon, in which two model dyes (AO7 and AG25) were competitively adsorbed onto beads of chitosan grafted with diethylenetriamine [ 41 ]. Langmuir and Freundlich equations were run for fitting.…”
Section: Modified Chitosans For Dye Adsorptionmentioning
confidence: 99%
“…The CTSN‐beads is prepared according to our previous research . First, a chitosan solution was prepared by dissolving 4 g chitosan flakes into 96 g of a 4% (m/m) acetic acid solution.…”
Section: Methodsmentioning
confidence: 99%
“…It is an effective way to enhance the adsorption of chitosan by introducing more amino groups. In our previous work, porous chitosan beads were synthesized by grafting diethylenetriamine on the surface of chitosan; the results showed that modified chitosan has excellent adsorption efficiency in terms of acid dye molecules …”
Section: Introductionmentioning
confidence: 99%